Comparison Of Efficacy Of Intravenous Dexmedetomidine Vs Clonidine Vs Tramadol To Control Post Spinal Shivering In Parturiants Undergoing Elective Lscs (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION: – Post spinal shivering is very unpleasant, uncomfortable to the 55% population of parturient. Shivering is spontaneous, involuntary, rhythmic, tremor-like muscle hyperactivity that  increases metabolic heat production up to 600% after general or regional anaesthesia. There  are various methods available to control shivering during anaesthesia. We conducted this both  drugs control post spinal shivering. In present study to compare the relative efficacy of Dexmedetomidine, Clonidine and  Tramadol for control of intraoperative shivering under spinal anaesthesia Study design: Randomized double blind Observation study. AIMS AND OBJECTIVES: – The present study is undertaken to clinically compare the efficacy, haemodynamic effects,  complications and side effects of Dexmedetomidine, Clonidine & Tramadol on control of post  spinal shivering in parturient. METHODS: – After obtaining written informed consent, we conducted a randomised study in 90 parturient (30 in each group) and compared the efficacy of intravenous Dexmedetomidine Clonidine and  Tramadol for controlling post spinal shivering. Patients were given inj. Dexmedetomidine (Group D) 0.5mcg/kg, Injection clonidine (Group  C I.V. Clonidine 0.5mcg/kg), Tramadol (Group T- I.V. Tramadol 1mg/kg) when shivering of  grade 2 to 4 was noted which lasted for minimum periof of 2 minutes after institution of  subarachnoid block. CONCLUSION: Dexmedetomidine, Clonidine& Tramadol effectively treated patients with  post spinal shivering, but time taken for complete cessation of shivering was earlier in  Tramadol. From our study we conclude that, I.V Tramadol is a better alternative than I.VAlpha 2agonists (Dexmedetomidine & Clonidine) in treatment of post spinal anaesthesia shivering
Keywords: Iv Clonidine; Iv Dexmedetomidine; I.v Tramadol; Lscs; Parturients. Post Spinal Shivering